(untitled) (مجلة إحالات, 2026)
In this paper we hope to establish a contrast between the classical Arabic morphological theory and modern morphology regarding the analysis of a word, whether it is a verb or a noun. That by looking at the set of concepts and techniques terms on which each of the two. The purpose of this contrast is not the extent of a theory in relation to the other but rather it is to present two very different models and their difference is not due to the temporal dimension but rather to two cognitive backgrounds that make us deepen the research on morphological analysis.